Institutional Quality, Geopolitical Risk, and Trade Openness in Pakistan - Javaid Hussain; Ali, Hammad; Hassan, Zubair ul; Faheem, Muhammad (iRASD Journal of Economics, 2024)
The present study investigates how institutional quality and geopolitical risk affect trade openness in Pakistan from 1998 to 2023, using the autoregressive distributive lag (ARDL) technique. Trade openness (TRO) is the dependent variable, while institutional quality, geopolitical risk, financial development (FD), and the real effective exchange rate (REER) are independent variables. Long-run results show that geopolitical risk and the real effective exchange rate negatively impact trade, whereas institutional quality (IQ) and financial development (FD) have positive effects. In the short run, geopolitical risk and financial development negatively influence trade, while institutional quality and the real effective exchange rate positively affect it. The study recommends that policymakers focus on improving institutional quality and refining real effective exchange rate mechanisms to enhance trade openness in Pakistan. Additionally, addressing geopolitical risks is crucial for achieving sustainable and improved trade outcomes.